(untitled) (FUDMA JOURNAL OF SCIENCES, 2023)
The study evaluates the dietary composition in flesh of Archachatina marginata var saturalis and Tympanotonus fuscatus (Radula) bought from road side hawkers in Nsukka L.G.A. of Enugu State. An experimental study of the dried matter of both sampled species were carried out using proximate analysis in accordance to AOAC. The results showed that the dried matter of A. marginatavar. saturalis flesh has protein content of (86.96 ± 0.37%), fat (7.35 ± 0.24), fibre (5.06 ± 0.03), carbohydrates (4.56 ± 0.45) and ash (1.88 ± 0.19), moisture (1.54 ± 0.21), whereas in T. fuscatusvar. radula the carbohydrates content was observed as (21.52 ± 1.50), protein content (25.96 ± 0.56), ash (16.30 ± 1.09), fat (8.36 ± 0.29), moisture (7.86 ± 0.39) and fibre (1.53 ± 0.76). The two samples revealed high protein content in A. marginatavar. saturalis and in T. fuscatus carbohydrate is equally high with least low value in ash and fibre respectively. This showed that A. marginatavar. saturalis is very rich in protein than T. fuscatus var. radula. Consumption of the species meat will provide the body with these essential nutrients that is needed for majorities of the cell activities and body build up and growth for both old and young by incorporating into our diets.